Public services in India: Issues of neutrality vs. commitment - Shamshad, Ahmad (2006)
One largely unexplored angle in the growing inefficiency and depravity of our administrative system is the much debated politician-civil servants nexus. Even former Cabinet Secretary, Subramanyam conceded that in recent years, the bureaucracy has buckled here and there as it never did in the past. Recent controversies involving minister-civil servant relationship have raised doubts both in the academic circles and in the public mind. In the years after Independence, political neutrality of the bureaucracy was, by and large, respected, both by the bureaucracy and the political leadership. With the end of one party domination at the Centre, the politicisation of the bureaucracy became apparent. A natural corollary to the desire of the political leadership to use their power for partisan political ends was the politicisation of the bureaucracy. It has been suggested that the "excessive responsibility given to the ministers ... induces civil servants to keep their political masters in good humour". The most relevant issue related with the higher civil services in India today is the issue of political neutrality, anonymity and commitment of civil services. - Reproduced.
Keywords: Civil service - India; Civil service